Analysis and Characterization of Thermal-Piezoresistive MEMS Resonators. (2016) - Coelho, C.; Gaspar, J.; Rocha, L.
Abstract: Thermal-piezoresistive MEMS resonators based on internal thermal-piezoresistive amplification are a suitable alternative for sensing applications, since they enable high resonant frequencies and high-Q factors at ambient pressure. In this work, thermal-piezoresistive MEMS resonators are fabricated, analyzed and experimentally characterized for a better understanding of the several domains involved. The analysis performed includes analytical and FEM modeling combined with experimental data to fully characterize the resonators. While FEM simulations are used to characterize the thermal domain, experimental measurements were performed to obtain the characteristics of the electrical (properties as resistivity and longitudinal coefficient of piezoresistivity, πl), and mechanical domain (resonant frequencies and Q factors). The set of simulation and experimental results can be used to design novel high-frequency resonators, for sensing applications, with improved performance due to internal thermo-piezoresistive amplification.